Nitrogenous compounds balance and microbial protein synthesis in steers supplemented with sunflower crushed in partial replacement of soybean meal - doi: 10.4025/actascianimsci.v35i3.18654 - Hellen Leles Lima; Rafael Henrique de Tonissi e Buschinelli de Goes; Euclides Reuter de Oliveira; Maria Gizelma de Menezes Gressler; Kelly Cristina da Silva Brabes; Andrea Maria de Araújo Gabriel (Acta Scientiarum. Animal Sciences, 2013)
Four steers in individual paddocks with Marandu grass (B. Brizantha) in 4x4 square designwere used to evaluate sunflower crushed supplementation in pasture-grazing animals on nitrogen balanceand microbial protein synthesis. Supplements at 6 g kg-1 body weight comprised corn, soybean meal, andmineral and soybean meal substituted at proportions 0, 20, 40 and 60%. Diet contained averages 6.79, 6.96,7.10 and 6.87% nitrogen respectively for substitution levels 0, 20, 40 and 60%. The inclusion of sunflowercrushed (SC) increased nitrogen intake and fecal excretion of nitrogen while providing a positive balance.Animals’ plasma urea concentration supplemented with SC was 28.13% lower than that of supplementedanimals without SC. SC inclusion did not change allantoin concentration, purine derivatives, microbialnitrogen, crude microbial protein and microbial efficiency microbial, with mean rates totaling 150.98 mmolday-1; 158.06 mmol day-1, 112.35 g day-1, 702.18 g day-1; 146.41 crude protein (CP) microbial kg-1 of TDN.Partial replacement of soybean meal by sunflower crushed improves nitrogen balance without alteringmicrobial protein synthesis and excretion of urea and creatinine